Recent Advances in Organic-inorganic Hybrid Photoresists - Zhihao Wang; Xindi Yao; Huiwen An; Yake Wang; Jinping Chen; Shuangqing Wang; Xudong Guo; Tianjun Yu; Yi Zeng; Guoqiang Yang; Yi Li (Journal of Microelectronic Manufacturing, 2021)
Photoresists are radiation-sensitive materials used for forming patterns to build up IC devices. To date, most photoresists have been based on organic polymers, which have been dominating the semiconductor industries over the past few decades. It is obvious that extreme ultraviolet (EUV) lithography has become the next-generation lithography technology. The development of comprehensive performance EUV resist is one of the most critical issues. However, organic polymeric photoresists are difficult to meet the harsh requirements of EUV lithography. Pure inorganic photoresists such as metal salts, hydrogen silsesquioxane (HSQ) are expected for EUV lithography due to their high resistance and high resolution. But the low sensitivity makes them not suitable for high volume manufacturing (HVM). Organic-inorganic hybrid photoresists, containing both organic and inorganic components, are regarded as one of the most promising EUV resists. They combine both merits of organic and inorganic materials and have significant advantages in machinability, etching resistance, EUV absorption, and chemical/thermal stability. Organic-inorganic hybrid photoresists are considered as ideal materials for realizing industrial-grade patterns below 10 nm. This review mainly focuses on the development of organic-inorganic hybrid photoresists over the past decade.